2011
DOI: 10.4314/ejhs.v21i2.69049
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Site Infection Rate and Risk Factors among Obstetric Cases of Jimma University Specialized Hospital, Southwest Ethiopia

Abstract: BackgroundSurgical Site infections are the second most frequently reported infections of all nosocomial infections among hospital patients. Among surgical patients in obstetrics, Surgical Site Infections were the most common nosocomial infections and the rate is higher in sub-Saharan Africa. There has not been a study which documented the extent of the problem in the study area; hence the objective of this study was to determine the surgical site infection rate among women having surgery for delivery in obstet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

34
113
8
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(166 citation statements)
references
References 17 publications
34
113
8
6
Order By: Relevance
“…8 Obstetric care services should be strengthened in rural areas. 59% of the patients were nulliparous which is similar to that of study in Mitt et al 9 Tran et al reported that the risk factor of surgical site infection was shown to be reduced by 39% and 60% when women had one or more children respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8 Obstetric care services should be strengthened in rural areas. 59% of the patients were nulliparous which is similar to that of study in Mitt et al 9 Tran et al reported that the risk factor of surgical site infection was shown to be reduced by 39% and 60% when women had one or more children respectively.…”
Section: Discussionmentioning
confidence: 99%
“…10 Majority of the cases were unbooked which correlates with Amenu D et al study. 8 Antenatal care provides opportunities for health education, prior detection and correction of maternal problems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In present study prevalence of SSIs was 11.1% in gynaecological procedures while it was 9.1% in obstetric procedures. Amenu D et al [9] observed an overall surgical site infection rate of 11.4% among women having surgery for Obstetric reasons. Devjani et al [11] observed the incidence as 24.2% following lower segment caesarean section while in similar studies Ansar A et al [13] Ghuman et al [15], Vijayan et al [16] observed the prevalence as 5.8%, 5% and 4.1% respectively.…”
Section: Discussion:-mentioning
confidence: 99%
“…Various studies have shown that emergency cases land up in SSI more than the elective ones [17][18][19][20][21][22][23]. Amenu D et al [9] in their study observed Surgical Site Infections rate to be two times higher in emergency procedures as compared to that of elective cases. Kishwar N et al [18] also observed emergency caesarean sections as risk factor for development of SSI.…”
Section: Discussion:-mentioning
confidence: 99%